Girlfriendship and sameness: affective belonging in a digital intimate public. Issue 3 (4th May 2017) - Kanai, Akane
Abstract: This article draws on Lauren Berlant's conceptualization of an intimate public to explain how the culture of postfeminist girlfriendship in a set of blogs on Tumblr invites particular pleasures based on desires for normativity and commonality. This digital intimate public is based on the circulation, adaptation and readership of a central popular blog named WhatShouldWeCallMe authored by two 'best friends' narrating humorous, everyday moments of youthful feminine experience through blog posts made up of GIFs and captions. This blog has also inspired other self-representative adaptations of its format authored by other young women, capturing funny, self-deprecating and intimate snapshots of life. Through an affective-discursive analysis of WhatShouldCallMe and five of its adaptations, I find that the intimacy of this public is based on the fantasies of feminine sameness that Berlant identifies, but there are distinctive practices through which this intimate generality may be achieved in a digital setting. Knowledge, labor and skill are required to craft generic selves through which attachments to a normative girlfriend sameness may be fostered.